Experimental study of Thermoelectric Energy Harvesting. (February 2020) - Subramanyam, J; Bhanodaya Reddy, G; Raghavendra, N; Vijayasimha Reddy, B G
Abstract: Waste heat energy harvesting aims to supply electricity to electric or electronic systems from different energy sources present in the environment without grid connection or utilization of batteries. These energy sources are solar (photovoltaic), movements (kinetic), radio-frequencies and thermal energy (thermoelectricity). The thermoelectric energy harvesting technology exploits the Seebeck effect. This effect describes the conversion of temperature gradient into electric power at the junctions of the thermoelectric elements of a thermoelectric generator (TEG) device. This device is a robust and highly reliable energy converter, which aims to generate electricity in applications in which the heat would be otherwise dissipated. The significant request for thermoelectric energy harvesting is justified by developing new thermoelectric materials and the design of new TEG devices. Potential TEG applications as energy harvesting modules are used in medical devices, sensors, buildings and consumer electronics. Present work is experimental study and analysis of thermoelectric energy harvesting and their low-power applications, and calculation of figure of merit which is dimensional less number for deciding harvesting efficiency.